2016
DOI: 10.1002/2015ja022269
|View full text |Cite
|
Sign up to set email alerts
|

Performance of IRI‐2012 model during a deep solar minimum and a maximum year over global equatorial regions

Abstract: Present paper inspects the prediction capability of the latest version of the International Reference Ionosphere (IRI‐2012) model in predicting the total electron content (TEC) over seven different equatorial regions across the globe during a very low solar activity phase 2009 and a high solar activity phase 2012. This has been carried out by comparing the ground‐based Global Positioning System (GPS)‐derived VTEC with those from the IRI‐2012 model. The observed GPS‐TEC shows the presence of winter anomaly whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…His results showed that the diurnal VTEC prediction performance of the model is generally better during the solar minimum phase 2009 than during solar maximum phase 2012 which is in agreement to this study (Tariku et al 2014). Kumar (2016) studied IRI-2012 model with respect to ground based GPS measurements during ascending phase of solar activity in 2009 to 2013 from low to mid-latitudes and they found that low-latitude regions higher than mid-latitude discrepancies during all the seasons (Kumar et al 2015).…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…His results showed that the diurnal VTEC prediction performance of the model is generally better during the solar minimum phase 2009 than during solar maximum phase 2012 which is in agreement to this study (Tariku et al 2014). Kumar (2016) studied IRI-2012 model with respect to ground based GPS measurements during ascending phase of solar activity in 2009 to 2013 from low to mid-latitudes and they found that low-latitude regions higher than mid-latitude discrepancies during all the seasons (Kumar et al 2015).…”
Section: Introductionsupporting
confidence: 85%
“…The IRI-2016 model shows slightly small discrepancies in high solar activity phase (2012-2016) by overestimating or underestimating and correlating, which is expected because the IRI model is a model for the ionosphere and does not include the TEC contribution from the plasma sphere. The short coming of this analysis is that the plasmasphere TEC is not taken into account which can be computed using plasmaspheric model (Kumar 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This result is important because it was expected major discrepancies at nighttime due to the fact the IRI-TEC model does not include the effects from the plasmasphere. In general, the GPS-TEC computes the TEC from ground all the way up to the plasmasphere, but the IRI-TEC model includes the ionosphere to the maximum altitude of only 2000 km [Kumar, 2016;Kenpankho et al, 2011]. However, the larger discrepancies observed at SJC station in the afternoon hours for all months are possibly due to dynamics of EIA region in consequence of the equatorial fountain effect, which the IRI model fails to predict correctly.…”
Section: Variations Of Dtec (Difference Between Tec From Gps and Iri-mentioning
confidence: 83%
“…Then we can obtain the IPPs according to the coordinates of the stations and satellites. Afterward, the ground‐based GNSS slant total electron content (STEC) measurements, ground‐based LEO STEC measurements, and LEO‐based GNSS STEC measurements are simulated using a ionospheric electron density model (Bilitza et al, ; Kumar, ; Nava et al, ), for example, International Reference Ionosphere (IRI; http://www.irimodel.org/). In this paper, we use the latest version of IRI model, which is IRI2016 version (the download address of Fortran source code: http://www.irimodel.org/IRI-2016/).…”
Section: Methodsmentioning
confidence: 99%